Rauh ibin Zinbaa AL-Juthami and his role on Umayyad state policy - Mohammad AL – Azzi, Mohammad Fayyad (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This study shed light on phenomenon characteristic ,played important political and administrative role, who witnessed the disturbance which led to end of the Rashidit reign in Sufeen battle in ( 36 H/656A.B) and founded of the Umayyad state, its Rauh ibin Zinbaa AL-Juthami, which leave clearly impresses on the of that era. His influence on Umayyad policy beginning more clearly during Yazeed ibin Muaawia Ibin Abi Sufyan (61-63 A.H / 679-682 AD) in AIharaha battle and during conference of AL- Jabiah and the battle of Marrge Rahut (65 AH/684 AD)against adherents Abdulah ibin AL- Zubair in Damascus , then his consultation and his prevent in suitable time perhaps the Umayyad caliphate fall down, He worked governorate in : Baalbek , Madena ( in Hejaz) , Jordan Jund and Palestine Jund , then as a counselor for caliphate Abed AL- Malek ibin Marwan (65-86 H D / 684- 705 A D ) يسلط هذا البحث الضوء على شخصية بارزة لعبت دوراً سياسياً وإدارياً مهماً ، شهدت اضطرابات أودت بالخلافة الراشدية بعد معركة صفين ( 36ه / 656 م) وقيام الدولة الأموية ، إنه روح بن زنباع الجذامي ، الذي ترك بصمات واضحة في صفين(36هـ/ 656 م) والحرة(61- 63هـ / 679-682م ) ، ومؤتمر الجابية ، ومعركة مرج راهط (65هـ/ 684م) ضد أنصار عبد الله بن الزبير في دمشق . اذ لولا رأيه وتدخله في الأوقات المناسبة ربما سقطت الخلافة الأموية . عمل روح بن زنباع والياً على بعلبك ، والمدينة المنورة ، وجند الأردن ، وجند فلسطين ، ومستشاراً للخليفة عبد الملك بن مروان(65- 86 هـ / 684- 705م ).